Carbon Pricing Watch 2016 - World Bank Group (Washington, DC: World Bank, 2016)
The report is a one stop shop for learning about key developments and prospects of existing and emerging carbon initiatives. A challenging international carbon market has not stopped the development of domestic carbon pricing initiatives. Today, about 40 national and over 20 sub-national jurisdictions responsible for almost one fourth of global greenhouse gas emissions are putting a price on carbon. Together, these initiatives cover the equivalent of almost 6 gigatons of carbon dioxide, or about 12% of global emissions.